I need help solving the following equation-

-2/y+6(4)=6

I know this is a pretty basic equation, but my mind is blank. Any help would be appreciated THANKS !

Results 1 to 3 of 3

- Oct 28th 2008, 01:26 PM #1

- Joined
- Oct 2008
- Posts
- 2

- Oct 28th 2008, 03:30 PM #2

- Joined
- Apr 2005
- Posts
- 18,857
- Thanks
- 2705

The point of "solving an equation" is to get "y= something" which means you want to get rid of all the numbers on the left. 6(4)= 24 so this is really -2/y+ 24= 6. That "24" is added so we can get rid of it by doing the opposite: subtract 24 from both sides of the equation: -2/y+ 24-24= 6- 24 or -2/y= -18. The "2" is multiplied and the opposite of multiplying is dividing: (-2/y)/-2= -18/(-2) or 1/y= -9. Now invert: reverse each fraction: y= -1/9.

- Oct 28th 2008, 03:59 PM #3

- Joined
- Oct 2008
- Posts
- 2